Dual-Band, Dual-Polarized Two Element Slot Antenna for Fifth Generation Mobile Devices (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper presents a two-element dual-band MIMO antenna with dual-polarization for 5G user equipment. Both operating frequencies are of sub-6 GHz band centered at 3.6 GHz and 5.5 GHz respectively and are independent of each other. Antenna polarizations depend on the placement of the feed elements on the PCB. The antenna is designed on FR-4 substrate to ensure its easy availability and keeping it cost-effective. The resultant radiation pattern of the antenna set is bi-directional with good gain and efficiency.